DESIGN OF A MONITORING SYSTEM FOR SOLAR-POWERED PUBLIC STREET LIGHTING - Kelvin; Endah Setyaningsih; Hadian Satria Utama (TESLA: Jurnal Teknik Elektro, 2024)
Street lighting is an essential facility that ensures the comfort and safety of road users at night. PJU can utilize resources from PLN electricity, solar energy, or a combination of both (hybrid). Solar-Powered Street Lighting fully utilizes solar energy (off-grid) or partially (hybrid) for its energy needs. However, the efficiency of solar panels tends to decrease during operational periods due to negative temperature coefficients, mechanical loads, and weather conditions. Additionally, the lithium-ion batteries used in PJUTS degrade over time. Therefore, a monitoring system is needed to measure the performance of PJUTS, ensure timely maintenance for solar panels and batteries, and maintain the performance of the Solar Charge Controller during the battery charging and discharging cycles. The INA219 sensor is used to simultaneously read current and voltage. Data from this sensor (current and voltage of the solar panels, battery during charging, and battery during discharging) is sent to a web server via WiFi using the ESP32 microcontroller with the HTTP GET method. The data received by the web server is stored in a MySQL database. A web page then displays the real-time PJUTS data retrieved from the database, processed into graphs and tables that can be accessed based on specific dates. Testing shows that the INA219 sensor has a small deviation compared to the Fluke multimeter, with an average voltage deviation of 0.046V and an average current deviation of 0.93 mA Abstrak Penerangan jalan umum merupakan fasilitas penting yang memastikan kenyamanan dan keselamatan pengguna jalan pada malam hari. PJU dapat menggunakan sumber daya dari listrik PLN, energi matahari, atau kombinasi keduanya (hybrid). Penerangan Jalan Umum Tenaga Surya sepenuhnya memanfaatkan energi matahari (off-grid) atau sebagian (hybrid) untuk kebutuhan energinya. Namun, efisiensi panel surya cenderung menurun selama masa operasional akibat koefisien suhu negatif, beban mekanis, dan kondisi cuaca. Selain itu, baterai lithium-ion yang digunakan dalam PJUTS mengalami degradasi seiring waktu. Oleh karena itu, diperlukan sistem pemantauan untuk mengukur kinerja PJUTS, memastikan perawatan tepat waktu untuk panel surya dan baterai, serta menjaga kinerja Solar Charge Controller dalam siklus pengisian dan pemakaian baterai. Sensor INA219 digunakan untuk membaca arus dan tegangan secara bersamaan. Data dari sensor ini (arus dan tegangan panel surya, baterai saat pengisian, dan baterai saat pemakaian) dikirim ke server web melalui WiFi menggunakan mikrokontroler ESP32 dengan protokol HTTP metode GET. Data yang diterima server web disimpan dalam basis data MySQL. Halaman web kemudian menampilkan data real-time PJUTS yang diambil dari basis data, diolah menjadi grafik dan tabel yang dapat diakses berdasarkan tanggal tertentu. Pengujian menunjukkan bahwa sensor INA219 memiliki deviasi kecil terhadap multimeter Fluke, dengan rata-rata deviasi tegangan sebesar 0,046V dan rata-rata deviasi arus sebesar 0,93 mA